Labeless and reversible immunosensor assay based upon an electrochemical current-transient protocol - Grant, Sarah; Davis, Frank; Pritchard, Jeanette A.; Law, Karen A.; Higson, Seamus P. J.; Gibson, Timothy D. (Elsevier Science B.V., Amsterdam., 2003)
A novel labeless and reversible immunoassay based upon an electrochemical current-transient protocol is reported which offers many advantages in comparison to classical immuno-biochemical analyses in terms of simplicity, speed of response, reusability and possibility of multiple determinations. Conducting polypyrrole films containing antibodies against 1) Bovine Serum Albumin (BSA) and 2) Digoxin were deposited on the surface of platinum electrodes to produce conductive affinity matrices having clearly defined binding characteristics. The deposition process has been investigated using 125I labelled anti-digoxin to determine optimal fabrication protocols. Antibody integrity and activity, together with non-specific binding of antigen on the conducting matrix have also been investigated using tritiated digoxin to probe polypyrrole/anti-digoxin films. Amperometric responses to digoxin were recorded in flow conditions using these films, but the technique was limited in use mainly due to baseline instability. Anti-BSA - polypyrrole matrices were investigated in more detail in both flow and quiescent conditions. No observable response was found in flow conditions, however under quiescent conditions (in non-stirred batch cell), anti-BSA – polypyrrole films have been demonstrated to function as novel quantitative chronoamperometric immuno-biosensors when interrogated using a pulsed potential waveform. The behaviour of the electrodes showed that the antibody/antigen binding and/or interaction process underlying the response observed was reversible in nature, indicating that the electrodes could be used for multiple sensing protocols. Calibration profiles for BSA demonstrated linearity for a concentration range of 0-50 ppm but tended towards a plateau at higher concentrations. Factors relating to replicate sensor production, sample measurement and reproducibility are discusse